Changes in the methane emissions and hard coal output in the Brzeszcze mine (the Upper Silesian Coal Basin, Poland) - Dreger, Marcin (Geology, Geophysics and Environment, 2020)
The paper presents the variability of methane emissions in mining excavations in the Brzeszcze mine (Poland) against the background of hard coal output, geological and mining factors. The geological structure of the Upper Silesian Coal Basin (USCB) is very diverse. The Brzeszcze coal deposit is located close to the large and permeable Jawiszowice fault which increases the methane hazard during mining activities performed close to this fault. The overall decrease in hard coal output (1988–2018) has coincided with a rapid increase in methane emissions (1997–2018). Throughout the study period, hard coal output decreased threefold from 3.9 to 1.2 million Mg annually. Coal extraction in high methane content beds (e.g. 510, 405/1, 364, 352) increases the total methane (CH4) emission into mining excavations, aggravating the methane hazard due to the high explosiveness of the gas. To protect miners, coal workings need to be continuously ventilated, taking the harmful gas out of the mine (ventilation air methane emission) or methane needs to be captured by underground methane systems (degassing). Every year, over 34 million m3 of CH4 is captured by the drainage systems and over 70 million m3 CH4 (average) is discharged through ventilation shafts into the atmosphere. The presence of the large, permeable regional dislocation, the Jawiszowice fault zone, shaped the methane concentration in the fault vicinity, when the highest methane emissions during coal mining was studied.